Actuation system design with electrically powered actuators - Meng, Fanliang (Cranfield University, 2011)
This project addresses the actuation system architecture of future All-electric aircraft (AEA) with electrically powered actuators (EPA). Firstly, the information of EPAs is reviewed, and then an electro-hydrostatic actuator (EHA) and electro-mechanical actuator (EMA) are selected for further system research. The actuation system architecture of Boeing and Airbus is then presented as a conventional design where the new design concepts are also researched and the distributed architecture was proposed as another design trend. To find out which one is better, both of them are selected for further research. The easily available data makes the Flying Crane a better choice for the case study. Stall load, maximum rate and power are the main elements for electric actuator requirements and power consumption, weight, cost and safety are the most important aspects for civil aircraft actuation systems. The conventional and distributed flight actuation system design considered the redundancy of systems and actuators, and also the relationship of the power, control channel and actuator work mode. But only primary flight actuation control system specifications are calculated since this data has better precision and also the limited time has to be taken into consideration. Brief comparisons of the two system specifications demonstrate that the higher power actuator have has higher efficiency and distributed actuators could reduce the system weight through reduce the system redundancy with a power efficiency decline. The electrically powered actuation system for future aircraft design is a balance between actuator number, system weight and power consumption.
Keywords: EHA; EHA; conventional; distributed; architecture; PWR